(3GdJMQjQs - (3CHh WGdH jMji Hf GdMSjf Hf gGQhf GdgGQhfj,J (B404 (3g` s ((3YKeGf Hf SYO GdSMGei s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeJg hSfi ehgHJg SCdJ habc Gddg hEjGfG dWGYJg , hJdNjU ePGgH GdbGSe Hf EHQGgje , hjMi Hf GdMSjf hChdGOgeG s
(3BNQgG (B:s
(3aEf CSde Ndi SHjdg , hEf CHG bJd hEf cGf cGaQkG ai GdCUd hdMb HOGQ GdMQH Ydi caQg ESJQb Je GdcJGH HMeOGddg Gdedc GdhgGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg GdgOhjI (B162) s
Keywords: (3abg GdePGgH GdCNQis